The early intervention dictionary : a multidisciplinary guide to terminology - Coleman, Jeanine G. 4 0 16; 5 (Bethesda, MD : Woodbine House, 2006)
Provides definitions for over 4,000 of the most commonly used medical, therapeutic, and education terms covering a number of subject areas including counseling, early childhood, social work, psychology, and audiology.
Adult.
Keywords: 2 -- 0; 6; Developmentally disabled children;Early childhood education -- 20 -- Terminology.;Terminology.; 20; 2